Bioclinical Parameters Driving Decision-Making of Subsequent Lines of Treatment in Metastatic Castration-Resistant Prostate Cancer. (27th May 2014) - Irelli, A.; Bruera, G.; Cannita, K.; Palluzzi, E.; Gravina, G. L.; Festuccia, C.; Ficorella, C.; Ricevuto, E.
Abstract : Different options are available as second-line treatment of metastatic castrate-resistant prostate cancer: cabazitaxel, abiraterone, and enzalutamide. Phase III studies evaluating cabazitaxel and the two hormonal agents have been shown to significantly prolong overall survival compared to mitoxantrone and placebo, respectively. Several studies have also demonstrated feasibility and activity of docetaxel rechallenge in case of a sufficient progression-free interval (3–6 months), good performance status, and previous acceptable safety profile, thus providing an additional treatment option in clinical practice. Clinical and biological parameters should be considered to tailor II line treatment. In clinical practice, we can primarily evaluate patients' fitness according to age, performance status, symptomatic disease, comorbidities, and expected safety profile of each drug. Different prognostic/predictive factors may be considered, such as presence of bone-limited or visceral metastases, length of androgen deprivation therapy (ADT) before chemotherapy, time to progression after docetaxel, Gleason score, PSA doubling time, and serum testosterone, even if their clinical relevance is still debated. This review will discuss current options of innovative drugs sequencing and selection according to bioclinical parameters.